An Unusual Long-Term Survey of a Patient with Widespread Malignant Urachal Tumor, Not Given Chemotherapy or Radiotherapy - Tugrul Ormeci; Murat Can Kiremit; Bulent Erkurt; Aslı Örmeci (Case Reports in Radiology)
The urachus establishes a connection between the dome of the bladder and the umbilicus throughout fetal life. If the urachus does not close completely, malignancy is a potential complication. The primary treatment for malignant urachal tumor is surgical excision. A 61-year-old male patient diagnosed with urachal carcinoma had undergone partial cystectomy 25 years previously. Twenty years later, local recurrence was treated with another partial cystectomy without umbilical remnant excision. Recurrence at the umbilical site was excised 2 years later, but intraperitoneal invasion had occurred, and the patient underwent a total colectomy at that time. Local disease and disseminated metastases in the thorax and intra- and extraperitoneal areas were noted upon admission to our hospital. Urachal carcinomas are usually aggressive tumors, and surgical treatment should include partial or radical cystectomy and excision of the urachus and umbilicus, to prevent local recurrence and distant metastasis.